Multidirectional speed in youth soccer players: theoretical underpinnings - McBurnie, A. J.; Dos`Santos, T. (Strength and Conditioning Journal, 2022)
This review provides a definition for multidirectional speed (MDS) and evaluates its technical and mechanical underpinnings. This review explores each component of MDS while considering unique aspects of youth physiology and epidemiology. With a theoretical understanding of MDS, practitioners will be more informed on the planning and periodization of MDS training methods in soccer. MDS comprises linear speed, change of direction speed, curvilinear speed, contextual speed, and agility, which each have distinct physiological, biomechanical, and neurocognitive distinctions that can either be differentiated or harmonized to optimize training.